1996
DOI: 10.1080/15216549600201041
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of 4‐(2,6‐dichlorophenyl)‐1,2,5‐thiadiazol‐3‐yl‐N‐methyl, N‐ethylcarbamate on replication of human immunodeficiency virus type 1 and the mechanism of action

Abstract: SummaryIn the search for effective antiviral agents, we have found 4-(2, 6-dichlorophenyl)-l, 2, 5-thiadiazol-3-yl-N-methyi, N-ethylcarbamate (RD4-2025) to be a highly potent and selective inhibitor of human immunodeficiency virus type 1 (HIV-1) in vitro. The 50% effective concentration of RD4-2025 for HIV-l-induced cytopathic effect in MT-4 cells was 37 nM, yet no antiviral activity was observed against HIV-2. In HIV-1 reverse transcriptase (RT) assays, RD4-2025 inhibited both RNA-dependent and DNAdependent D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…There is a long-standing interest in the study of molecules that contain organic heterocycles of nitrogen and one of the chalcogens (sulfur, selenium, or tellurium) due to their many actual and proposed applications, in addition to their sometimes unusual chemistry. In the case of the 1,2,5-chalcogenadiazole ring, the sulfur derivatives can be used in antibacterial and antiviral agents, insecticides, fungicides, specialized polymers, and organic LEDs; , the corresponding selenium compounds are also applicable as antibacterials, fungicides, , and insecticides ,, in addition to dyes. All three benzo-2,1,3-chalcogenadiazoles have been investigated as building blocks in supramolecular design because of their propensity to associate through secondary bonding interactions. …”
Section: Introductionmentioning
confidence: 99%
“…There is a long-standing interest in the study of molecules that contain organic heterocycles of nitrogen and one of the chalcogens (sulfur, selenium, or tellurium) due to their many actual and proposed applications, in addition to their sometimes unusual chemistry. In the case of the 1,2,5-chalcogenadiazole ring, the sulfur derivatives can be used in antibacterial and antiviral agents, insecticides, fungicides, specialized polymers, and organic LEDs; , the corresponding selenium compounds are also applicable as antibacterials, fungicides, , and insecticides ,, in addition to dyes. All three benzo-2,1,3-chalcogenadiazoles have been investigated as building blocks in supramolecular design because of their propensity to associate through secondary bonding interactions. …”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported the thiadiazole derivatives as novel HIV-1-specific RT inhibitors (Fujiwara et al, 1997;Ijichi et al, 1995). Studies of the mechanism of action have revealed that the thiadiazole derivatives belong to the family of NNRTIs (Ijichi et al, 1996). In this report, we evaluated the genotypic and phenotypic changes of RD4-2217-resistant strains.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the mechanism of action have revealed that the thiadiazole derivatives belong to the family of NNRTIs (Ijichi et al, 1996). In this report, we evaluated the genotypic and phenotypic changes of RD4-2217-resistant strains.…”
Section: Discussionmentioning
confidence: 99%
“…This is achieved by exposing the chromosomes to a concentrated solution of formamide at high temperatures, 70 to 80°C, for a few minutes, followed by the addition of the probe which is then allowed to hybridize for multiple hours at 37°C in a formamide solution. Formamide is a useful denaturant as it lowers both the stability and melting point of DNA linearly as the concentration of formamide increases [4]. This hybridization period has been recently shortened to only a few minutes with the use of a microwave; however, the use of formamide in the staining solution was still used [5].…”
Section: Introductionmentioning
confidence: 99%